THE INFLUENCE OF DIFFERENT WING MOTIONS ON THE LIFT IN BIO-INSPIRED AERIAL VEHICLES - Visona Carnielo, Bianca Tais [UNESP]; Bueno, Douglas D. [UNESP] (My University, 2024)
With the recent applications of micro aerial vehicles for civil and military use, the interest in non conventional aerodynamic designs is growing, in this context, the bio-inspired aerial vehicles show some advantages when compared with the fixed and rotary-wings aircraft, such as noise reduction, efficiency and reduced size. Identifying the aerodynamic principles that allow species of birds, insects and bats to fly can bring tools for aircraft development, since these species make use of aerodynamic principles different from those used in engineering. Once one of the challenges of building bio-inspired UAVs (unmanned aerial vehicles) is modeling the aerodynamics of flapping wings, the present work uses the UVLM (Unsteady Vortex Lattice Method) to obtain the aerodynamic forces and pressure values for two different wings configuration inspired by the Great black backedgull (Larus marinus) and by the Blue-and-yellow macaw (Ara Ararauna). The influence of the wing movements of flapping, pitching, heaving and spanning and folding on the aerodynamic performance of the wing is analyzed through the lift and thrust/drag coefficients.
Keywords: aerodynamic; bio-inspired; flapping wings; UAV; UVLM